The impact of detraining on cardiac autonomic function and specific endurance and muscle power performances of high-level endurance runners - Pereira, L. A.; Nakamura, F. Y.; Castilho, C.; Kitamura, K.; Kobal, R.; Cal Abad, C. C.; Loturco, I. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to analyze the effects of four weeks of training cessation (TC) on specific endurance performance, resting and postexercise heart rate variability (HRV) and neuromuscular capacities of high-level endurance runners.